THE INFLUENCE OF TOTAL ASSETS, INFLATION, THE BANKâS INDONESIA CERTIFICATE, AND THE EXCHANGE RATE ON THE RETURN SHARE OF BANKING COMPANIES REGISTERED AT THE INDONESIA STOCK EXCHANGE - Poli, Aryati (JURNAL KEBANGSAAN, 2013)
The objectives this research to analyse the influence of total assets, inflation, the banks Indonesia certificate, and the exchange rate on the return share of banking companies registered at the Indonesia stock exchange. The sample that was used in this research totalling 16 banking companies registered at the Indonesia stock exchange during the year 2009-20012, that choiced was based on the method purposive sampling. The analysis method that used multiplied regression. Analysis carried out for the interval of the 6 monthly and 12 monthly. The analyst results showed that inflation and exchange rate to have influence on the return share of banking companies for the interval of the 6 monthly, Whereupon in the interval of the 12 monthly only exchange rate variables to have influence on the return share of banking companies. Afterwards simultaneously was found that total assets, inflation, the banks Indonesia certificate, and the exchange rate to have influence on the return share of banking companies in the interval of the 6 monthly, and 12 monthly. Keywords: total assets, Inflation, the banks Indonesia certificate, and the exchange rate, return share.